(untitled) (Semiárida, 2020)
It was used fertilization at sowing (40 kg/ha of N), at sowing of the end of tillering (40 kg/ha of N in each stage) and at early heading (40 kg/ha of N). Grain yields and its components: heads per m2, heads per plant, spikelets per head, grain per spikelets and 1000 seeds weight was determinate. The correlations analyzed showed high positive association between heads per m2 and grain yield r= 0,93) for Buck Pucará and r= 0,71 for Buck Cencerro. The results obtained indicate lack of response in cultivars and in the chosen fertilizing moment. There are compensation effects between yield components.